City Branding Design from the Identification of Local Values of Penajam Paser Utara Regency - Tajri M, Fulkha; Ngabito, Olivia Febrianty; Huldiansyah, Denny; Sherlia; Yendra, Sasferi (Universitas Ciputra, 2023)
Penajam Paser Utara Regency is in a strategic location to improve its brand identity. Its existence adjacent to the new State Capital (IKN) is an opportunity with great potential for developing all Penajam Paser Utara Regency (PPU) sectors. The natural wealth in the form of the sea, endemic fauna in the form of sambar deer, Mastogok traditional motifs and some rice-producing areas that can be said to be the granary of IKN food security are local values that will be visualized in the form of a logo that characterizes Penajam Paser Utara Regency, plus a location that can be said to be